(untitled) (Research, Society and Development, 2020)
Several models of conduction of passion fruit branches have been used to obtain increases in productivity and improvement in fruit quality. The objective of this work was to evaluate the development of plants and productivity of yellow passion fruit grafted in two conduction systems of the lateral secondary branches. The experiment was conducted at a farm in the municipality of Adamantina, SP, from May, 2017 to June, 2018, adopting a randomized block design, in a 3 x 2 factorial scheme, with four replications and four plants per plot. The evaluated factors were three methods of propagating yellow passion fruit: seeds, grafting in P. gibertii obtained by seeds and grafting in P. gibertii obtained by cuttings, and two conduction systems, with one and two secondary branches. The height of the plants, the diameter of the stem of the rootstock and graft, the length of the secondary branches, the number of fruits per plant, the fruit mass and productivity were evaluated. The largest diameters and the longest lateral secondary branches were found in plants obtained by seeds. The propagation method used did not affect the number of fruits per plant and the productivity of yellow passion fruit. It was found that plants obtained by seeds develop more than plants grafted on P. gibertii, but that do not affect the productivity of the yellow passion fruit. Plants conducted with one or two lateral secondary branches do not interfere with the development and productivity of yellow passion fruit.